(untitled) (Medico Legal Update, 2020)
This study aimed for molecular characterization of local isolates of L. tropica and L. major and their relatedness to reference isolated from neighboring countries. Exudates and dermal tissues were collected from the cutaneous lesions of 50 newly diagnosed patients with CL. Leishmania DNA was extracted from lesion exudate and 5.8S rRNA gene was amplified using two sets of specific primers through nested PCR. A total of 12 PCR products were directly sequenced and the resultant sequences were aligned with reference sequences in National Center for Biotechnology Information (NCBI). A phylogenetic tree was constructed for local Leishmania isolates with the reference isolates using Mega 6 software. According to alignment results out of 12 sequences, 9 sequences were belonging to L. major, while 3 sequences were belonging to L. tropica. All local L. major isolates were very close to reference isolate KP773404.1 (an Iranian isolate), while all local L. tropica isolates were very close to reference isolate KY612611.1 (an Iranian isolate) with an identity of 98%. Phylogenetic trees confirmed that closest isolates for local Leishmania (whether L. tropica or L. major) was the Iranian isolate. These data indicate that local isolates of L. tropica and L. major are closely related to Iranian isolates.